Class XII Students' Perceptions of Swimming Learning at Darussalam Vocational School Karangpucung in the 2022/2023 Academic Year - Kusmiyati Kusmiyati; Dwi Septian; Understand Qirom (Universitas Sebelas Maret, 2023)
This research aims to find out how positive the perception of class This type of research is quantitative descriptive research with a survey method. The instrument used was a questionnaire on students' perceptions of swimming lessons in class XII of Darussalam Vocational School Karangpucung for the 2022/2023 academic year. Data validation uses the product moment formula with r hit > r tab (0.234). Reliability using Cronbach alpha is 0.870. The subjects in this research were 42 class XII students. The data analysis technique uses descriptive statistical analysis with a percentage formula. Based on the overall research results, it was concluded that students' perceptions of swimming learning in class and medium 14.2%. Meanwhile, the perception for the negative category was 28.5% with the percentage of external factors being negative 28.5% and very negative 14.2%. So it can be said that the perception of Darussalam Karangpucung Vocational School students is in the positive category.